Neospora caninum Infection Triggers S-phase Arrest and Alters Nuclear Characteristics in Primary Bovine Endothelial Host Cells - Velásquez, Zahady D.; Rojas-Barón, Lisbeth; Larrazabal, Camilo; Salierno, Marcelo; Gärtner, Ulrich; Pervizaj-Oruqaj, Learta; Herold, Susanne; Hermosilla, Carlos; Taubert, Anja (Frontiers in Cell and Developmental Biology, 2022)
Neospora caninum represents a major cause of abortive disease in bovines and small ruminants worldwide. As a typical obligate intracellular apicomplexan parasite, N. caninum needs to modulate its host cell for successful replication. In the current study, we focused on parasite-driven interference with host cell cycle progression. By performing DNA content-based cell cycle phase analyses in N. caninum-infected primary bovine umbilical vein endothelial cells (BUVEC), a parasite-driven S-phase arrest was detected at both 24 and 32 h p. i., being paralleled by less host cells experiencing G0/G1 cell cycle phase. When analyzing S-subphases, proliferation cell nuclear antigen (PCNA)-based experiments showed a reduced population of BUVEC in late S-phase. Analyses on key molecules of cell cycle regulation documented a significant alteration of cyclin A2 and cyclin B1 abundance in N. caninum-infected host endothelial cells thereby confirming irregularities in S-phase and S-to-G2/M-phase transition. In line to cell cycle alterations, general nuclear parameters revealed smaller nuclear sizes and morphological abnormalities of BUVEC nuclei within N. caninum-infected host cell layer. The latter observations were also confirmed by transmission electron microscopy (TEM) and by analyses on lamin B1 as a marker of nuclear lamina which illustrated an inhomogenous nuclear lamin B1 distribution, nuclear foldings and invaginations thereby reflecting nuclear misshaping. Interestingly, the latter finding applied to both non-infected and infected host cells within a parasitized BUVEC layer. Additionally, actin detection indicated alterations in the perinuclear actin cap formation since typical nucleo-transversal filaments were consistently lacking in N. caninum-infected BUVEC as also documented by significantly decreased actin-related intensities in the perinuclear region. These data indicate that N. caninum indeed alters host cell cycle progression and severly affects the host cell nuclear phenotype in primary bovine endothelial host cells. In summary, these findings add novel data on the complex N. caninum-specific modulation of host cell and nucleus thereby demonstrating clear differences in cell cycle progression modulation driven by other closely related apicomplexans like Toxoplasma gondii and Besnotia besnoiti.